University Campus Facilities and University Brand Image: Their influence on Interest in College - Rozikin, Achmad Zainul; Ilham; Syarif, Ahmad; Utari, Fiarika Dwi; Sartika, Nyimas Yuhanis; Suyati, Endang Sri (Jurnal Pendidikan Ekonomi Undiksha, 2025)
Higher education serves as an advanced stage of education following completion of secondary education. Despite this, many adolescents in Central Kalimantan show limited interest in pursuing higher education at local campuses. Various factors influence this phenomenon, among which are the quality of university campus facilities and the perceived brand image of universities in Central Kalimantan. This study examines three variables: university campus facilities, university brand image, and interest in college. The study population comprises all students of Muhammadiyah University of Palangkaraya, totaling 308 individuals. Results indicate that interest in college is partially and simultaneously influenced by both university campus facilities and university brand image. Notably, university brand image demonstrates a stronger contribution compared to university campus facilities in shaping students' interest in pursuing higher education.